The function and regulatory mechanism of RNA-binding proteins in breast cancer and their future clinical treatment prospects - Lu, Xingjia; Zhong, Jian; Liu, Linlin; Zhang, Wenzhu; Zhao, Shengdi; Chen, Liang; Wei, Yuxian; Zhang, Hong; Wu, Jingxuan; Chen, Wenlin; Ge, Fei (Frontiers in Oncology, 2022)
Breast cancer is the most common female malignancy, but the mechanisms regulating gene expression leading to its development are complex. In recent years, as epigenetic research has intensified, RNA-binding proteins (RBPs) have been identified as a class of posttranscriptional regulators that can participate in regulating gene expression through the regulation of RNA stabilization and degradation, intracellular localization, alternative splicing and alternative polyadenylation, and translational control. RBPs play an important role in the development of normal mammary glands and breast cancer. Functional inactivation or abnormal expression of RBPs may be closely associated with breast cancer development. In this review, we focus on the function and regulatory mechanisms of RBPs in breast cancer, as well as the advantages and challenges of RBPs as potential diagnostic and therapeutic targets in breast cancer, and discuss the potential of RBPs in clinical treatment.